Obesity and infection - the challenge of tropical medicine - Mota Pinto, Anabela (2016)
The World Health Organization currently considers obesity a worldwide epidemic. A perspective of the past considered overeating and a sedentary lifestyle as main factors of this major public health problem. However, other risk factors can be associated, such as heredity, sleep disorders and the action of microbial agents. Regarding the association of obesity with infection, it appears that some microorganisms such as viruses, bacteria, parasites and tropical microbial agents (e.g. chagas disease and cutaneous leishmaniasis) are markedly related to human obesity, and it has been shown that obese individuals have an altered response to infections. The mechanism behind the adipogenic action of these microorganisms varies from the effect on the central nervous system, to the modification of metabolism of adipose tissue. Obesity and the consequent expansion of adipose tissue alter imune system function, which may lead to an increased susceptibility to infection by various microorganisms. In summary, there is a close interrelationship between the adipose tissue, the immune-inflammatory response and infection, being conceivable that in response to certain infections, adipose tissue expands and reacts in a similar way to the expansion of immune system cells. Obesity decreases the immune response of adipose tissue, which modifies the patocronia of infections.